LITERASI DIGITAL DALAM PENELUSURAN INFORMASI PADA PERPUSTAKAN UNTUK SISWA DI SMK 8 PAB SAMPALI - Rahman, Idzhari; Syamanta, Arbana; Muhatri, Muhatri; Hutagalung, Muhammad Abrar Kasmin; Aditya, Elsa; Rustam, Muhammad Taufiq (Publikasi Pengabdian Masyarakat, 2024)
The cause of the increase in online access to information is the availability of internet technology in libraries. So the results of community service are outlined in the title Digital Literacy in Information Retrieval in the Library for Students at SMK PAB 8 Sampali, which is expected to provide success in managing the quality of excellent service at SMK PAB 8 Sampali. The development of digital technology and also the awareness of public information freedom and information dissemination have brought many changes to the pattern of handling collections and information in libraries. The existence of digital libraries and the spread of the internet and its access in various places, as well as the availability of millions of databases, but with the existence of analog collections, printed in the form of books, magazines, and other scientific works, it will have a good impact on the library, as well as provide the latest information services for students at SMK PAB 8 Sampali in meeting their information needs in the library. The final goal of all these processes is so that students at SMK PAB 8 Sampali can utilize information easily, information needs to be organized with the right search system by information managers who have expertise in information management systems and by utilizing information and communication technology in the library.